Constraints to leisure-time physical activity among Brazilian workers - Andrade R.D.* (2019)
© 2017, © 2017 Australia and New Zealand Association of Leisure Studies.The aim of this study was to identify perceived constraints to leisure-time physical activity (LTPA) most prevalent in Brazilian workers. Furthermore, this study aimed to analyze the types of constraints perceived in the practice of LTPA that better characterize the behaviour of active and insufficiently active workers. The study included 885 workers from a Brazilian industry. The level of physical activity and constraints practiced were analyzed, as well as sociodemographic data and work-related health factors. The most frequently perceived constraints to LTPA were ‘long working hours’ (60.3%), ‘family commitments’ (58.1%), and ‘housework’ (54.5%). Intrapersonal constraints better explained the behaviour of insufficiently active workers; moreover, for those with a regular physical activity, the constraints were environmental and structural. Long working hours and excess housework reflect low levels of physical activity in workers. The model of leisure constraints was confirmed in Brazilian workers with different levels of physical activity.